2014
DOI: 10.1002/glia.22708
|View full text |Cite
|
Sign up to set email alerts
|

Molecular targeting of TRF2 suppresses the growth and tumorigenesis of glioblastoma stem cells

Abstract: Glioblastoma is the most prevalent primary brain tumor and is essentially universally fatal within two years of diagnosis. Glioblastomas contain cellular hierarchies with self-renewing glioblastoma stem cells (GSCs) that are often resistant to chemotherapy and radiation therapy. GSCs express high amounts of repressor element 1 silencing transcription factor (REST), which may contribute to their resistance to standard therapies. Telomere repeat-binding factor 2 (TRF2) stablizes telomeres and REST to maintain se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 64 publications
0
26
0
Order By: Relevance
“…66 GSCs were enriched using established stem cells marker CD133 from primary GBMs and U251-GBM cells by labeling with PE-conjugated CD133 antibody and sorting by flow cytometry. Although other putative stem cell markers were used previously to enrich GSCs including SSEA-1, 67 CD44 68 and integrin α 6 69 and L1CAM, 70 CD133 has been shown to be a widely used marker of self-renewing and tumorigenic GBM cells, 6,7173 therefore, we have used this marker in our studies. To induce the differentiation, CD133-postive GSCs were cultured in 10% FBS for 7 days.…”
Section: Methodsmentioning
confidence: 99%
“…66 GSCs were enriched using established stem cells marker CD133 from primary GBMs and U251-GBM cells by labeling with PE-conjugated CD133 antibody and sorting by flow cytometry. Although other putative stem cell markers were used previously to enrich GSCs including SSEA-1, 67 CD44 68 and integrin α 6 69 and L1CAM, 70 CD133 has been shown to be a widely used marker of self-renewing and tumorigenic GBM cells, 6,7173 therefore, we have used this marker in our studies. To induce the differentiation, CD133-postive GSCs were cultured in 10% FBS for 7 days.…”
Section: Methodsmentioning
confidence: 99%
“…46 An isoform of REST, hREST4, counters the genesilencing effect of REST in a dominant negative fashion. Depending on the cell context, TRF2 could either stabilize REST to maintain self-renewal of NSCs, 46,48 or prevent hREST4 from ubiquitin-mediated proteasomal degradation to promote neuronal differentiation. 46,49 A dominant negative form of TRF2 triggers a DNA damage response and senescence in mitotic neural cells and TRF2 inhibition enhances the differentiation of hippocampal neurons.…”
Section: Nuclear Role Of Trf2mentioning
confidence: 99%
“…In particular, we and others showed that in the cytoplasm of neurons, TRF2-S binds and stabilizes REST, in turn maintaining the self-renewal of NSCs, 17,48 or binds the truncated, dominant negative isoform hREST4, thus promoting neuronal differentiation. 46,49 In addition, TRF2-S binds and sequesters REST in the cytoplasm of neurons to antagonize REST nuclear activity and to maintain neuronal traits.…”
mentioning
confidence: 99%
“…There is another report by Bai et al which showed the role of TRF2 in maintenance of neurospheres in glioblastoma multiforme (GBM) [18].…”
Section: Ivyspringmentioning
confidence: 99%